Investigating a Teacher’s Beliefs and Practices in Teaching Grammar: A Case Study of a Senior Teacher of English in a High School in Jakarta - Syaadiah Arifin (Universitas Pendidikan Ganesha, 2023)
What a teacher believes and does in grammar instruction is a substantial issue that needs to be explored. Understanding the teacher's beliefs could facilitate a better understanding of the teacher's classroom practices and, eventually, the nuances of her student's performance. A few studies have been conducted on a teacher's beliefs and practices in teaching grammar in the Indonesian context. However, studies investigating a senior teacher's beliefs and practices in teaching grammar are infrequent in Indonesia. The teaching of grammar has always been controversial for language teachers in L2/ EFL settings. The main problem is how grammar should be taught and acquired. The aim of this study is to analyze a teacher's beliefs and practices relating to the teaching of grammar. The data were gathered through an in-depth interview with the teacher and classroom observations. This research focused only on a female senior teacher who has taught English for tens of years in a high school environment. From the in-depth interview and the observations, the researcher obtained meaningful information from the teacher, starting from the beginning of her teaching, then during the Post Method phase, and through the phase for the integration of the teaching of grammar with technology. From the interviews and classroom observations, the researchers can conclude that the teacher has shown consistency with her beliefs, and the several teaching innovations while still adopting the Deductive Method.